Antiproton collisions with excited positronium - Michael Charlton (Physical Review A, 2023)
We present results of calculations of several processes resulting from positronium (Ps) collisions with antiprotons: antihydrogen formation, Ps breakup, and nPs-changing collisions. Calculations utilize the quantum convergent close-coupling (CCC) method and the classical trajectory Monte Carlo (CTMC) method. We identify a region of Ps principal quantum numbers nPs and Ps energies where the classical description is valid and where the CCC calculations become computationally too expensive. This allows us to present the most complete and reliable set of cross sections in a broad range of nPs and initial orbital momentum quantum numbers lPs which are necessary for experiments with antihydrogen at CERN.